Three spiritual narratives: A reading of Hermann Hesse, Ibn Tufayl and Naguib Mahfouz - Khattab, Muna Moataz (AUC Knowledge Fountain, 2017)
The current thesis examines how narrative form harmoniously coordinates the motif and the physical nature of the fabula to present three levels of the journey, the physical, the metaphorical and the narratological. This study offers a reading of three novels, Hermann Hesse’s Siddhartha, Ibn Tufayl’s Hayy Ibn Yaqzan and Naguib Mahfouz’s The Journey of Ibn Fattouma. These novels are spiritual journeys that suggest how literature can be read as narrative. My use of narratology throughout this thesis engages the role of the fabula and the function of metaphor in the overall development of each novel. My analysis relies on the theoretical principles and definitions set forth by Gerald Prince in Dictionary of Narratology and Mieke Bal in Narratology: An Introduction. Both critics have dealt with the interaction between fabula and narrative in their contribution to narrative theory. Vladimir Propp’s more formulaic method has been used in this thesis to analyze the structure of each novel.